The History of Thestudy of the Kazakh Altai Paleolithic in the Years Independences (Journal of history, 2019)
Тhe article describes the history of the study of the stone age of the Kazakh Altai. From the year of independence to the present day, East Kazakhstan attracts special attention of scientists. To date, about 20 new monuments of the Paleolithic period have been discovered, such as Kurchum, Kuigan, Sereimbai, Rysak 1, Kozybai 1-2, Ushbulak1-2, etc. it should be noted that among the listed monuments of special attention of scientists, the recently opened Parking lot Ushbulak-1 is a multilayer stratified monument ever discovered in this region. The study of this monument has been conducted since 2016 by the joint Russian-Kazakh expedition of Institute of archeology and ethnography of Siberian branch of Russian academy of sciences and the National Museum of the Republic of Kazakhstan. In the course of the work, several already known and new monuments of the stone age with surface and layered deposits of archaeological material were further investigated. To date, the work of the joint expedition is carried out in a planned manner.